2015
DOI: 10.1038/ncomms6984
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic mismatch sorts SNARE proteins into distinct membrane domains

Abstract: The clustering of proteins and lipids in distinct microdomains is emerging as an important principle for the spatial patterning of biological membranes. Such domain formation can be the result of hydrophobic and ionic interactions with membrane lipids as well as of specific protein–protein interactions. Here using plasma membrane-resident SNARE proteins as model, we show that hydrophobic mismatch between the length of transmembrane domains (TMDs) and the thickness of the lipid membrane suffices to induce clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 70 publications
(121 reference statements)
5
140
0
2
Order By: Relevance
“…A mismatch between the length of the transmembrane domain and the lipid bilayer can also induce the clustering of Sx1A (ref. 26). Single-molecule imaging analysis of Sx1A expressed in spinal cord neurons revealed that Sx1A mobility is more restricted at synapses when compared with extrasynaptic sites2728.…”
mentioning
confidence: 99%
“…A mismatch between the length of the transmembrane domain and the lipid bilayer can also induce the clustering of Sx1A (ref. 26). Single-molecule imaging analysis of Sx1A expressed in spinal cord neurons revealed that Sx1A mobility is more restricted at synapses when compared with extrasynaptic sites2728.…”
mentioning
confidence: 99%
“…The neuronal plasma membrane SNARE syntaxin-1a may be more soluble in Ld than in Lo phase membranes (Bacia et al, 2004) because of different lipid ordering (Murray and Tamm, 2009) or because of hydrophobic mismatch (Milovanovic et al, 2015). Interestingly, the cholesterol-dependent clustering of syntaxin-1a is further modulated by electrostatic interactions with negatively charged lipids including phosphatidylserine (PS) and phosphatidylinositol-(4,5)-bisphosphate (PIP 2 ) (Murray and Tamm, 2009, 2011; van den Bogaart and Jahn, 2011).…”
Section: Effect Of Cholesterol On Snare-mediated Intracellular Membramentioning
confidence: 99%
“…Briefly, membrane curvature necessary for vesicular formation is facilitated by hydrophobic mismatch as results of protein crowding, as well as scaffolding mechanisms with the aid of coat proteins [36*]. Hydrophobic mismatch causes proteins, which have large extramembrane components diffusing in the membrane, to induce molecular crowding in order to lower the accessible membrane surface area and reduced lipids [37].…”
Section: Interplay Between Lipids and Proteins In Vesicular Formationmentioning
confidence: 99%